SOCIALIZATION EXPERIENCES AND AGENTS-PARTNERS IN SHAPING THE COLLEGE STUDENT-INTERPACES OF ACADEMIC PRODUCTIVITY - Oliveira, Maisa Aparecida; Silveira Galan Fernandes, Maria Cristina [UNESP] (Univ Metodista Piracicaba-unimep, 2016)
The work aims to analyze the impacts of academic productivity in students' education, in which problematize the social and university policy, directed to their spaces of socialization and training dimensions, ethics. The survey was conducted with 120 undergraduate students Biological Sciences, Humanities and Exact the Institution of Brazilian Higher Education sciences centers who responded to a questionnaire. Subsequently, 10% of students held a semi-structured interview. Data analysis was guided by critical perspectives. The university legitimizes and reproduces relations of social domination, focusing on how the school trajectory student influences the dynamic of their activities at the university, conditioning the choices and attitudes in developing their personal and professional formation. We conclude that students have incorporated the practice of knowledge production that follows the logic of intensified and productivist work of academics, driven commodification of knowledge in the context of neoliberal policies. The student activity is reduced to the academic and scientific activity, with low rate of participation in social groups of college.
Keywords: PRODUCTIVITY OF HIGHER EDUCATION; UNIVERSITY STUDENT; ACADEMIC TRAINING